Factors Affecting Profitability on Animal Feed Companies in Indonesia - Mercky Haryo; Amzul Rifin; Bunasor Sanim (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
The animal feed industry is essential as it supports livestock industry in meeting the need of protein of a country. Feed contribution reaching at 70 percent of livestock production cost makes feed becomes an pivotal factor which could boost its sales. Unfortunately net income of animal feed companies for the last five years tent to decrease and emerged problems. The aim of this study were to examine internal and external factors affecting profitability represented by ROA and formulate recommendations in improving them. The results showed that internal factors affecting ROA significantly are Sales, COGS, and TATO, while for the external factor is exchange rate. DAR, inflation and international corn prices do not influence ROA significantly. The implications for companies and animal feed industries in improving profitability generally is by increasing sales and TATO value. Also, the company must be able to press COGS especially raw material cost which is more sensitive to profitability when its price is higher. Companies have to conduct risk management in order to anticipate exchange rate volatility followed by government’s action as regulator in maintaining macroeconomic and trade stability.